Inhibition of EGFR, HER2, and HER3 signalling in patients with colorectal cancer wild-type for BRAF, PIK3CA, KRAS, and NRAS (FOCUS4-D): a phase 2–3 randomised trial. (March 2018) - Adams, Richard; Brown, Ewan; Brown, Louise; Butler, Rachel; Falk, Stephen; Fisher, David; Kaplan, Richard; Quirke, Phil; Richman, Susan; Samuel, Leslie; Seligmann, Jenny; Seymour, Matt; et al.
Summary: Background: A substantial change in trial methodology for solid tumours has taken place, in response to increased understanding of cancer biology. FOCUS4 is a phase 2–3 trial programme testing targeted agents in patients with advanced colorectal cancer in molecularly stratified cohorts. Here, we aimed to test the hypothesis that combined inhibition of EGFR, HER2, and HER3 signalling with the tyrosine kinase inhibitor AZD8931 will control growth of all wild-type tumours. Methods: In FOCUS4-D, we included patients from 18 hospitals in the UK with newly diagnosed advanced or metastatic colorectal cancer whose tumour was wild-type for BRAF, PIK3CA, KRAS, and NRAS . After 16 weeks of first-line therapy, patients with stable or responding tumours were randomised to oral AZD8931 (40 mg twice a day) or placebo. Randomisation was done by minimisation with a random element of 20%, minimisation by hospital site, site of primary tumour, WHO performance status, 16-week CT scan result, number of metastatic sites, and first-line chemotherapy regimen. The primary outcome was progression-free-survival. CT scans were assessed by local radiologists according to Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1. Preplanned interim analyses were assessed per protocol and were agreed using multiarm multistage (MAMS) trial design methodology triggered by occurrence of progression-free survival events in the placebo group. The final analysis was assessed by intention to treat. This trial is registered atcontrolled-trials.com, ISRCTN 90061546. Findings: Between July 7, 2014, and March 7, 2016, 32 patients were randomised to study treatment, 16 to AZD8931 and 16 to placebo. At the first preplanned interim analysis (March, 2016), the independent data monitoring committee (IDMC) recommended closure of FOCUS4-D because of a lack of activity. At the final analysis (Aug 1, 2016), 31 patients had had a progression-free survival event (15 with AZD8931 and 16 with placebo). Median progression-free survival was 3·48 months (95% CI 1·51–5·09) in the placebo group and 2·96 months (1·94–5·62) in the AZD8931 group. No progression-free survival benefit of AZD8931 compared with placebo was noted (hazard ratio [HR] 1·10, 95% CI 0·47–3·57; p=0·95). The most common grade 3 adverse event in the AZD8931 group was skin rash (three [20%] of 15 patients with available data vs none of 16 patients in the placebo group), and in the placebo group it was diarrhoea (one [7%] vs one [6%]). No grade 4 adverse events were recorded and no treatment-related deaths were reported. Interpretation: The MAMS trial design for FOCUS4 has shown efficiency and effectiveness in trial outcome delivery, informing the decision to proceed or stop clinical evaluation of a targeted treatment within a molecularly defined cohort of patients. The overarching FOCUS4 trial is now aiming to open a replacement arm in the cohort with all wild-type tumours. Funding: Medical Research Council (MRC) and National Institute for Health Research (NIHR) Efficacy and Mechanism Evaluation programme, Cancer Research UK, NIHR Clinical Trials Research Network, Health and Care Research Wales, and AstraZeneca.